“We Can Speak for Ourselves”: An Applied Theatre Workshop About Decolonization for Judges - Jerke, Lauren; Arcand, Rupert; Ward, Rocky (Percées)

(untitled) (Société québécoise d'études théâtrales (SQET), 2023)
This article is about how we developed and delivered a full-day applied theatre workshop about decolonization for judges. The workshop first provided a framework for judges to take into account Canada’s colonial history and the ongoing colonial ideas that manifest within us at the individual level. Next, the workshop offered judges an opportunity to step outside of their usual professional roles and consider how the needs of an Indigenous youth are addressed in court from the perspective of the young person and their grandmother. The purpose of our workshop was to collectively consider what it means to decolonize ourselves and our justice system. This case study demonstrates that “rules of engagement” are flexible, yet must be supported with cultural knowledge, respect for cultural protocol, reflection, respect for lived experience, and an openness to learning by all.